The interaction of a supersonic plasma jet containing nanoparticles with a substrate - Kravchenko, O.Yu.; Maruschak, I.S. (Вопросы атомной науки и техники, 2021)
In the framework of a multi-fluid axisymmetric hydrodynamic model, the interaction of a supersonic plasma jet containing nanoparticles with a flat substrate is investigated using computer simulation. In particular, the fluxes of nanoparticles on the substrate are studied at plasma inlet pressure P₀=1…100 Torr. The results show that a shock wave is formed near the substrate, which affects the energy of nanoparticles and their fluxes on the substrate. The width of the region along the radius, where the flow of nanoparticles onto the substrate is essential, depends on the plasma pressure in the jet. At large values of plasma pressure (P₀≥75 Torr) a cloud of nanoparticles with a sharp boundary is formedon the axis of the plasma jet near the substrate. Interacting with this cloud, nanoparticles moving in the plasma jet, lose directed energy and their flow on the substrate near the axis of the jet is zero. У рамках багаторідинної осесиметричної гідродинамічної моделі досліджується взаємодія надзвукового струменя плазми, що містить наночастинки, з плоскою підкладкою за допомогою комп’ютерного моделювання. Зокрема, потоки наночастинок на підкладку вивчаються при плазмовому тиску на вході P₀=1…100 Topp. Результати показують, що поблизу підкладки утворюється ударна хвиля, яка впливає на енергію наночастинок та їх потоки на підкладку. Ширина області по радіусу, де потік наночастинок на підкладку є суттєвим, залежить від тиску плазми в струмені. При великих значеннях плазмового тиску (P₀≥75 Торр) на осі плазмового струменя поблизу підкладки утворюється згусток наночастинок з різкою межею. При взаємодії з цим згустком наночастинки, які рухаються в плазмовому струмені, втрачають спрямовану енергію, і їх потік на підкладку поблизу осі струменя дорівнює нулю. В рамках многожидкостной осесимметричной гидродинамической модели исследуется взаимодействие сверхзвуковой струи плазмы, содержащей наночастицы, с плоской подложкой с помощью компьютерного моделирования. В частности, потоки наночастиц на подложку изучаются при плазменном давлении на входе P₀=1…100 Topp. Результаты показывают, что вблизи подложки образуется ударная волна, которая влияет на энергию наночастиц и их потоки на подложку. Ширина области по радиусу, в которой поток наночастиц на подложку существенен, зависит от давления плазмы в струе. При больших значениях плазменного давления (Р₀≥75 Торр) на оси плазменной струи вблизи подложки образуется сгусток наночастиц с резкой границей. Взаимодействуя с этим сгустком, наночастицы, которые движутся в плазменной струе, теряют направленную энергию, и их поток на подложку вблизи оси струи равен нулю.